Menu Close

Category: Differential Equation

y-2-y-1-e-2x-1-2-

Question Number 26240 by sorour87 last updated on 22/Dec/17 $${y}^{\left(\mathrm{2}\right)} −{y}=\left(\mathrm{1}−{e}^{\mathrm{2}{x}} \right)^{\frac{−\mathrm{1}}{\mathrm{2}}} \\ $$ Commented by prakash jain last updated on 23/Dec/17 $${y}^{\left(\mathrm{2}\right)} −{y}=\left(\mathrm{1}−{e}^{\mathrm{2}{x}} \right)^{\frac{−\mathrm{1}}{\mathrm{2}}}…

y-2y-3-y-1-x-4yln-y-y-1-

Question Number 26127 by sorour87 last updated on 20/Dec/17 $${y}+\mathrm{2}{y}^{\mathrm{3}} {y}^{\left(\mathrm{1}\right)} =\left({x}+\mathrm{4}{y}\mathrm{ln}\:\left({y}\right)\right){y}^{\left(\mathrm{1}\right)} \\ $$ Answered by prakash jain last updated on 21/Dec/17 $${y}+\mathrm{2}{y}^{\mathrm{3}} \frac{{dy}}{{dx}}=\left({x}+\mathrm{4}{y}\mathrm{ln}\:{y}\right)\frac{{dy}}{{dx}} \\…

Question-91656

Question Number 91656 by jagoll last updated on 02/May/20 Commented by john santu last updated on 02/May/20 $$\frac{{dy}}{{dx}}\:=\:\frac{−\mathrm{3}{xy}−{y}^{\mathrm{2}} }{{x}^{\mathrm{2}} +{xy}}\:=\:\frac{−\frac{\mathrm{3}{y}}{{x}}−\left(\frac{{y}}{{x}}\right)^{\mathrm{2}} }{\mathrm{1}+\left(\frac{{y}}{{x}}\right)} \\ $$$$\left[\:{y}\:=\:{px}\:\Rightarrow\:\frac{{dy}}{{dx}}\:=\:{p}\:+\:{x}\frac{{dp}}{{dx}}\:\right] \\ $$$${p}\:+{x}\:\frac{{dp}}{{dx}}\:=\:\frac{−\mathrm{3}{p}−{p}^{\mathrm{2}}…